L’enquête paysagère, une méthode d’intelligibilité politique du monde ? - Sylvie Joublot Ferré (Projets de Paysage)
Because of the Anthropocene and the contemporary challenges facing our societies it is legitimate that the ways in which we inhabit the planet should be regularly questioned. Studying the landscape in the classroom could prove valuable in gaining a political understanding of our modes of inhabiting. The aim of this article is to give an account, based on a case study, of the heuristic dimension of the experience of the landscape in situ and of its potential for political education.